Development of Competency-Based Teaching Materials on Initial Value Problems and Boundary Conditions Course - Suanto, Elfis; Armis, Armis; Sari, Anita (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Most of the lecturers do not give great attention or not considered the importance of teaching materials. This is reinforced by the lack of existed teaching materials that to supports the lectures. This study aims to develop competency-based teaching materials in for the subjects of Initial Value Problem and Boundary Condition (IVPBC) to build students higher-order thinking skills. This research is a development research consisting of three main stages, namely preliminary analysis, product design, and development. The object of this research is competence-based teaching materials in the subject of the initial value problem and boundary condition itself. After designing the teaching materials, then it was tested and validated by experts. The instrument used is a validation sheet consisting of 35 statement items. The result of the research shows that all validators have approved every aspect of assessment of teaching materials that are (1) relevance, (2) accuracy, (3) completeness of the presentation, (4) presentation system, (5) conformity of the presentation with the demand of student-centered learning, (6) presentation technique, (7) Indonesian language compliance and (8) legibility and communicativeness. As the conclusion, the developed teaching materials are valid and can be used on a wide scale of teaching.